Feeding habits of the Harlequin Duck - Pool, W (Wildfowl, 1962)
This is a summary of observations on the behaviour of Harlequin Ducks Histrionicus histrionicus made by members of the Ulster North Iceland Expedition, leader J. Arnold Benington, from 7th to 15th July, 1961.